Standardization Methods for the Determination of Curcumin in Turmeric and Its Anticancer Activities : A Review - Imel Ramelia Hudaya; Vina Luthfiana Hasna; Febi Febriani Hasanah; Khamairah Azzahrawaani Hermawan; Vriezka Mierza (Sean Institute, 2023)
Cancer is one of the deadliest diseases in the world. Indonesia is a country with cancer rates that ranks 8th in Southeast Asia. Cancer that has the highest number of sufferers in Indonesian men is lung cancer, as much as 19.4 per 100,000 population, with an average death rate of 10.9 per 100,000. Meanwhile, for women, breast cancer is the highest cancer incidence rate, which is 42.1 per 100,000 population, with an average death rate of 17 per 100,000 population. Although chemotherapy remains a highly efficient way to treat cancer, it is the drawbacks related to its side effects that are often feared. Natural products such as plants are more beneficial for improving treatment results because they are safe and can minimize side effects on healthy cells. Herbal plants that are often associated with anticancer drugs are turmeric. Currently, several standardized methods have been developed to analyze curcumin in turmeric, and from these methods, there are advantages and disadvantages of each method. Therefore, selecting the analytical method is very important to get better results.